Preparation method and application of sulfur / nitrogen doped ordered mesoporous carbon material
By introducing sulfur and nitrogen heteroatoms into ordered mesoporous carbon materials and preparing sulfur/nitrogen doped ordered mesoporous carbon materials by using soft template method, the problem of low energy density is solved, and its electrochemical performance and application potential is significantly improved.
Patent Information
- Application Number
- CN202411968287.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-11
AI Technical Summary
The application of ordered mesoporous carbon materials in the field of supercapacitors is limited by the low energy density, which limits its application potential in this field.
Phenol, formaldehyde, and aminothiophene compounds were used as raw materials to prepare a phenolic modified amine through Mannich reaction, and it was used to introduce heteroatoms S and N into the modified phenolic resin, and combined with a soft template agent with sulfate anionic surfactant and a triblock copolymer to prepare a sulfur/nitrogen doped ordered mesoporous carbon material.
The electrochemical properties of ordered mesoporous carbon materials are significantly improved, including the improvement of specific capacitance and energy density, while maintaining good cycling performance and stability.
Smart Images

Figure BDA0005218893250000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of mesoporous carbon materials, and in particular relates to a preparation method and application of a sulfur / nitrogen doped ordered mesoporous carbon material. Background Art
[0002] Supercapacitors, also known as electrochemical capacitors, are a new type of energy storage device between traditional capacitors and secondary batteries. They have the characteristics of long cycle life, high specific capacity, and fast charge and discharge. As a new type of energy storage element, supercapacitors mainly use the double-layer energy stored at the electrode / electrolyte interface. Whether the double layer can be formed quickly and evenly at the two-phase interface is an important factor in measuring the quality of capacitors.
[0003] Ordered mesoporous carbon materials (OMCs) refer to a metastable carbon crystal nanostructured material with a pore size of 2-50nm, uniform pore size, and regular and orderly arrangement. Compared with traditional porous carbon, ordered mesoporous carbon materials have a smaller average pore size, more concentrated pore structure, high porosity, narrow pore size distribution, and the structure has the characteristics of short-range disorder at the atomic level and long-range order at the mesoscopic level. For ordered mesoporous carbon materials with regular and orderly pore arrangement, electrolyte ions can migrate freely in the pores, quickly form a double layer, weaken the capacitance dispersion effect, have strong charging and discharging capabilities, and show relatively excellent electrochemical capacitance performance.
[0004] The synthesis methods of ordered mesoporous carbon include hard template method and soft template method. The hard template method refers to first synthesizing a silicon-based mesoporous molecular sieve, then using the mesoporous molecular sieve as a template, injecting a carbon precursor into its pores to form a nanocarbon precursor / silicon dioxide composite, and then undergoing carbonization and de-templating to obtain a highly ordered mesoporous carbon material. The soft template method is also known as the organic-organic self-assembly method. Through the non-covalent bond force between the polymer block copolymer and the carbon precursor molecules, the carbon precursor undergoes further condensation and assembles into an ordered mesoporous structure with a surfactant, and then obtains an ordered mesoporous carbon material through carbonization. Although it is difficult to remove the template agent and the cost is high when preparing ordered mesoporous carbon by the soft template method, the pore structure of the carbon material prepared by this method is highly controllable, and the synthesis conditions do not cause damage to the carbon material by strong chemical effects. Therefore, it is a current research hotspot, such as the highly thermally stable ordered mesoporous carbon material and its preparation method disclosed in patent CN102275898B. The patent discloses a green synthesis method of a carbon material with an ordered mesoporous structure having high thermal stability. The material is citric acid as a catalyst. On the one hand, citric acid can catalyze the polymerization of phenolic resin. In addition, its rich carboxyl functional groups can also enhance the interaction between the carbon precursor and the surfactant. Patent CN105540566B discloses a method for preparing an ordered mesoporous carbon material. The patent uses a surfactant and a polymer to form a composite of an ordered structure, and uses a salt solution or a solid salt to reduce the solubility of the composite in the solution to precipitate it. The resulting precipitate is heated in air and heat-treated at high temperature in nitrogen or argon to obtain an ordered mesoporous carbon material.
[0005] The above is the preparation of ordered mesoporous carbon using the soft template method. By adjusting the carbon precursor, the type, concentration and reaction conditions of the surfactant, the pore size, pore structure and morphology of the mesoporous carbon material can be controlled to meet the diverse application needs. As a supercapacitor electrode material, the ordered mesoporous carbon material has a stable structure and excellent cycle performance, but its energy density is still low, which greatly limits the application of ordered mesoporous carbon materials in the field of supercapacitors. Therefore, it is necessary to further optimize the preparation of ordered mesoporous carbon by the soft template method, so as to effectively improve the energy density of the ordered mesoporous carbon material while maintaining good cycle performance. Summary of the invention
[0006] In order to solve the above-mentioned problem of low energy density, the present invention provides a method for preparing a sulfur / nitrogen-doped ordered mesoporous carbon material and its application. The sulfur / nitrogen-doped ordered mesoporous carbon material uses phenol, formaldehyde, and aminothiophene compounds as raw materials, and obtains a phenol-modified amine having an "aminothiophene group" placeholder at the ortho or para position of phenol through a Mannich reaction. The phenol-modified amine is then used to replace part of the phenol as a raw material for preparing a modified phenolic resin, and heteroatoms S and N are introduced into the modified phenolic resin molecules to improve the electrochemical properties of the finally obtained ordered mesoporous carbon. Under the synergistic effect of a soft template compounded with a sulfate anionic surfactant and a triblock copolymer, the electrochemical properties of the ordered mesoporous carbon are greatly improved.
[0007] In order to achieve the above purpose, the following technical solutions are adopted:
[0008] A method for preparing a sulfur / nitrogen doped ordered mesoporous carbon material comprises the following steps:
[0009] S1: Add phenol and aminothiophene compounds to a reaction kettle and mix them evenly, heat up and keep the temperature constant for the first time, drop formaldehyde aqueous solution, heat up and keep the temperature constant for the second time after the dropwise addition, and distill after the reaction to obtain a viscous liquid phenolic modified amine;
[0010] S2: heating phenol to melt, adding phenolic modified amine and mixing evenly, adding alkali solution and formaldehyde aqueous solution and mixing evenly, heating to react, cooling to room temperature after the reaction, adjusting pH, vacuum dehydration, and adding organic solvent to prepare a modified phenolic resin solution;
[0011] S3: dissolving the soft template in an organic solvent to prepare a template solution, adding the modified phenolic resin solution and mixing evenly, standing, drying, and carbonizing at high temperature to obtain a sulfur / nitrogen doped ordered mesoporous carbon material;
[0012] In step S3, the soft template is prepared by compounding a sulfate anionic surfactant and a triblock copolymer at a mass ratio of 0.08-0.1:1.
[0013] In step S1, the aminothiophene compound is selected from 1-thiophene-2-ylpropane-1-amine, 1-(thiophene-3-yl)ethylamine, 4-methyl-3-thiopheneamine, 2-thiophenemethylamine, 2-thiopheneethylamine, 3-thiophenemethylamine, 3-thiopheneethylamine, one or a combination of two or more thereof; preferably 2-thiophenemethylamine. The molar ratio of the phenol, formaldehyde, and aminothiophene compound is 1-1.2:1-1.5:1-1.5. The first heating is to 60-80°C. The concentration of the formaldehyde aqueous solution is 30-37wt%. The formaldehyde solution is dripped in 0.5-1h, the second heating is to 100-105°C, and the reaction time is 3-5h.
[0014] In step S2, the temperature is raised to 40-42°C for melting. The mass ratio of phenol, phenolic modified amine, alkali solution and formaldehyde aqueous solution is 1: 0.4-0.6: 0.30-0.35: 2-2.2. The concentration of the alkali solution is 15-20wt%, and the alkali solution is selected from one or a combination of two or more of potassium hydroxide aqueous solution, sodium hydroxide aqueous solution, potassium carbonate aqueous solution and sodium carbonate aqueous solution. The concentration of the formaldehyde aqueous solution is 30-37wt%. The temperature is raised to 70-80°C for reaction for 3-5h. The pH is adjusted to a neutral pH with a 0.5-1mol / L HCl solution. The organic solvent is selected from one or a combination of two or more of tetrahydrofuran, ethanol, methanol, isopropanol, n-butanol and ether. The concentration of the modified phenolic resin solution is 15-25wt%.
[0015] In step S3, the concentration of the soft template in the template solution is 5-8wt%. The triblock copolymer is selected from one or a combination of F127 and P123. The sulfate anion surfactant is selected from one or a combination of sodium dodecyl sulfate and sodium nonylphenol polyoxyethylene ether sulfate. The organic solvent is selected from one or a combination of two or more of tetrahydrofuran, ethanol, methanol, isopropanol, n-butanol, and ether. The mass ratio of the soft template and the modified phenolic resin is 10-15:100. The standing is standing at 20-30°C for 5-10h, and the drying is drying at 80-100°C for 10-24h. The high temperature carbonization is: under inertness, first heating to 350-400°C at a rate of 1-2°C / min and keeping warm for 0.5-2h, and then heating to 600-800°C at a rate of 1-2°C / min and continuing carbonization for 3-5h.
[0016] Phenolic modified amine is a modified product with a "aminothiophene group" placeholder group at the ortho or para position of phenol obtained by Mannich reaction, using phenol, formaldehyde, and aminothiophene compounds as raw materials. The present invention uses phenolic modified amine to replace part of phenol as the raw material for preparing modified phenolic resin, and introduces heteroatoms S and N into the modified phenolic resin molecules to improve the electrochemical properties of ordered mesoporous carbon. The present invention also uses a soft template agent compounded by sulfate anion surfactant and triblock copolymer at a mass ratio of 0.08-0.1:1 to greatly improve the electrochemical properties of ordered mesoporous carbon. It is speculated that the placeholder group on the phenolic modified amine molecule makes the interaction between the carbon source modified phenolic resin and the triblock copolymer too large, which is not conducive to the orderly arrangement of the modified phenolic resin near the hydrophilic group on the triblock copolymer, and reduces the orderly arrangement of the ordered mesoporous carbon pores, making the electrochemical performance improvement effect poor. The use of an appropriate amount of sulfate anion surfactant and triblock copolymer compounding can solve this problem without affecting other properties.
[0017] The present invention also provides the use of the sulfur / nitrogen doped ordered mesoporous carbon material prepared by the above sulfur / nitrogen doped ordered mesoporous carbon material preparation method as a supercapacitor electrode material.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The sulfur / nitrogen doped ordered mesoporous carbon material provided by the present invention first uses phenol, formaldehyde, and aminothiophene compounds as raw materials, and obtains a phenol-modified amine having an "aminothiophene group" placeholder at the ortho or para position of phenol through a Mannich reaction, and then uses the phenol-modified amine to replace part of the phenol as a preparation raw material for a modified phenolic resin, and introduces heteroatoms S and N into the modified phenolic resin molecules to improve the electrochemical properties of the finally obtained ordered mesoporous carbon. The electrochemical properties of the ordered mesoporous carbon are further improved under the synergistic effect of a soft template agent compounded with a sulfate anionic surfactant and a triblock copolymer. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0021] Example 1
[0022] S1: Add 1.2 mol of phenol and 1.3 mol of 2-thiophenemethylamine to a reaction kettle and mix them evenly. Heat the mixture to 80°C for the first time and keep the temperature constant. Add 105.4 g of 37 wt% formaldehyde aqueous solution (containing 1.3 mol of formaldehyde) dropwise for 1 hour. Heat the mixture to 100°C for the second time and keep the temperature constant for 5 hours. After the reaction is completed, remove the by-products by distillation to obtain a viscous liquid phenolic modified amine.
[0023] S2: Take 100g of phenol and heat it to 42°C to melt, add 60g of phenolic modified amine and mix evenly, add 35g of 20wt% sodium hydroxide solution and 220g of 37wt% formaldehyde aqueous solution and mix evenly, heat it to 75°C to react for 3h, cool it to room temperature after the reaction, adjust the pH to 7 with 1mol / L HCl solution, vacuum dehydrate, and add tetrahydrofuran to prepare a 20wt% modified phenolic resin solution;
[0024] S3: Dissolve 300g of a soft template prepared by mixing sodium dodecyl sulfate and F127 in a mass ratio of 0.1:1 in a mixed solvent of tetrahydrofuran / ethanol in a volume ratio of 5:1 to prepare a 5wt% template solution, add 500g of a 20wt% modified phenolic resin solution and mix evenly, let stand at 25°C for 10h, dry at 80°C for 12h, and in a nitrogen atmosphere, first heat to 350°C at a rate of 1°C / min and keep warm for 1h, then heat to 800°C at a rate of 1°C / min and continue carbonizing for 3h to obtain an ordered mesoporous carbon material.
[0025] Example 2
[0026] The rest is the same as Example 1, except that in step S1, 2-thiophenemethylamine is replaced by 3-thiophenemethylamine in an equal molar amount.
[0027] Example 3
[0028] The rest is the same as Example 1, except that in step S2, the amount of phenolic modified amine used is 50 g.
[0029] Example 4
[0030] The rest is the same as Example 1, except that in step S2, the amount of phenolic modified amine used is 40 g.
[0031] Example 5
[0032] The rest is the same as Example 1, except that in step S3, the soft template is compounded with sodium dodecyl sulfate and F127 at a mass ratio of 0.08:1.
[0033] Example 6
[0034] The rest is the same as Example 1, except that in step S3, the amount of template solution used is 200 g.
[0035] Example 7
[0036] S1: Add 1.2 mol of phenol and 1.3 mol of 3-thiophenemethylamine to a reactor and mix them evenly. Heat the reactor to 80°C for the first time and keep the temperature constant. Add 105.4 g of 37 wt% formaldehyde aqueous solution (containing 1.3 mol of formaldehyde) dropwise. After 1 hour of dripping, heat the reactor to 100°C for the second time and keep the temperature constant for 5 hours. After the reaction is completed, remove the by-products by distillation to obtain a viscous liquid phenolic modified amine.
[0037] S2: Take 100g of phenol and heat it to 42°C to melt, add 60g of phenolic modified amine and mix evenly, add 35g of 20wt% sodium hydroxide solution and 200g of 37wt% formaldehyde aqueous solution and mix evenly, heat to 80°C to react for 3h, cool to room temperature after the reaction, adjust the pH to 7 with 1mol / L HCl solution, vacuum dehydrate, add tetrahydrofuran to prepare a 20wt% modified phenolic resin solution;
[0038] S3: Dissolve 200g of a soft template prepared by mixing sodium dodecyl sulfate and F127 in a mass ratio of 0.08:1 in a mixed solvent of tetrahydrofuran / ethanol in a volume ratio of 5:1 to prepare a 5wt% template solution, add 500g of a 20wt% modified phenolic resin solution and mix evenly, let stand at 25°C for 10h, dry at 80°C for 12h, and in a nitrogen atmosphere, first heat to 350°C at a rate of 1°C / min and keep warm for 1h, then heat to 800°C at a rate of 1°C / min and continue carbonization for 3h to obtain an ordered mesoporous carbon material.
[0039] Comparative Example 1
[0040] The rest is the same as Example 1, except that in step S3, the soft template is compounded with sodium dodecyl sulfate and F127 at a mass ratio of 0.05:1.
[0041] Comparative Example 2
[0042] The rest is the same as Example 1, except that in step S3, the soft template is compounded with sodium dodecyl sulfate and F127 at a mass ratio of 0.12:1.
[0043] Comparative Example 3
[0044] S1: Take 100g of phenol and heat it to 42°C to melt, add 25g of 20wt% sodium hydroxide solution and 180g of 37wt% formaldehyde aqueous solution and mix well, heat it to 75°C to react for 1h, cool it to room temperature after the reaction, adjust the pH to 7 with 1mol / L HCl solution, vacuum dehydrate to obtain phenolic resin, add tetrahydrofuran to prepare a 20wt% resin mixed solution;
[0045] S2: 300g of a soft template prepared by mixing sodium dodecyl sulfate and F127 in a mass ratio of 0.1:1 is dissolved in an organic solvent prepared by mixing tetrahydrofuran / ethanol in a volume ratio of 5:1 to prepare a 5wt% template solution, 500g of a 20wt% resin mixture is added and mixed evenly, the mixture is allowed to stand at 25°C for 10h, dried at 80°C for 12h, and in a nitrogen atmosphere, the temperature is first raised to 350°C at a rate of 1°C / min and kept for 1h, and then the temperature is raised to 800°C at a rate of 1°C / min and carbonized for 3h to obtain an ordered mesoporous carbon material.
[0046] Comparative Example 4
[0047] S1: Add 1.2 mol of phenol and 1.5 mol of 2-thiophenemethylamine to a reactor and mix them evenly. Heat the reactor to 80°C for the first time and keep the temperature constant. Add 121 g of 37 wt% formaldehyde aqueous solution (containing 1.5 mol of formaldehyde) dropwise for 1 hour. Heat the reactor to 100°C for the second time and keep the temperature constant for 5 hours. After the reaction, remove the by-products by distillation to obtain a viscous liquid phenolic modified amine.
[0048] S2: Take 100g of phenol and heat it to 42°C to melt, add 25g of 20wt% sodium hydroxide solution and 180g of 37wt% formaldehyde aqueous solution and mix evenly, heat it to 75°C to react for 1h, cool it to room temperature after the reaction, adjust the pH to 7 with 1mol / L HCl solution, vacuum dehydrate to obtain phenolic resin, mix the phenolic resin with phenolic modified amine in a mass ratio of 1:0.6, add tetrahydrofuran to prepare a 20wt% resin mixture;
[0049] S3: Dissolve 300g of a soft template prepared by mixing sodium dodecyl sulfate and F127 in a mass ratio of 0.1:1 in an organic solvent prepared by mixing tetrahydrofuran / ethanol in a volume ratio of 5:1 to prepare a 5wt% template solution, add 500g of a 20wt% resin mixture and mix evenly, let stand at 25°C for 10h, dry at 80°C for 12h, and in a nitrogen atmosphere, first heat to 350°C at a rate of 1°C / min and keep warm for 1h, then heat to 800°C at a rate of 1°C / min and continue carbonizing for 3h to obtain an ordered mesoporous carbon material.
[0050] Application Examples
[0051] The ordered mesoporous carbon prepared in the embodiment and the comparative example was used to prepare a supercapacitor and assemble a symmetrical supercapacitor.
[0052] Preparation of supercapacitor electrodes: Weigh ordered mesoporous carbon, conductive agent (acetylene black), and binder (PVDF) in a mass ratio of 8:1:1, mix evenly, and place in a clean glass container. Then add dispersant N-methyl-2-pyrrolidone (NMP) dropwise, ultrasonically oscillate for 15 minutes, and stir until the mixture becomes a paste. Spread the prepared slurry evenly on the current collector nickel foam, and then place it in a vacuum drying oven at 110°C and dry it for 12 hours. Finally, place the completely dried electrode on a powder tablet press and keep it at a pressure of 16MPa for 60s to obtain the final electrode, then weigh it and calculate the mass of the ordered mesoporous carbon on the electrode.
[0053] Assembly of symmetrical supercapacitors: Among the prepared electrodes, select two pole pieces with equal mass of ordered mesoporous carbon, and put them into the battery shell in parallel in the order of electrode-diaphragm-electrode. Then add an appropriate amount of 6 mol / L KOH electrolyte and seal it to obtain a symmetrical supercapacitor assembled with CR 2025 button batteries. After standing for 12 hours, it can be subjected to electrochemical testing.
[0054] The ordered mesoporous carbon materials prepared in the above examples and comparative examples were tested for the following properties:
[0055] Specific surface area and pore structure: measured by NOVA 1000e pore structure specific surface area tester. The sample was degassed at 350℃ for 2h, and liquid nitrogen was used as the adsorption medium at 77K and relative pressure (P / P0) 10 -6 N2 adsorption was carried out in the range of -1, and the specific surface area and pore size distribution were obtained by BET equation and BJH equation, respectively.
[0056] Constant current charge and discharge test: The material was subjected to constant current charge and discharge test using a CHI660A electrochemical workstation. The test voltage range in the two-electrode system (assembled into a capacitor) was 0-1V. The constant current charge and discharge curve was used to calculate the energy density and specific capacitance at a current density of 1A / g, as well as the specific capacitance and capacity retention rate when the current density increased from 1A / g to 10A / g. The formula is as follows:
[0057] (1) C = IΔt / ΔVm
[0058] (2) E = 0.5 CV 2
[0059] Where C is the specific capacitance of the supercapacitor (F / g), I is the charge / discharge current (A), ΔV is the potential change after deducting the voltage drop (V), m is the total mass of the active materials in the two working electrodes (g), E is the energy density (Wh / kg), V is the test voltage (V), and Δt is the discharge time (s).
[0060] Cycle life test: The symmetrical supercapacitor assembled with electrodes was subjected to cycle life test using Neware BTS 6.0 secondary battery testing system, with test voltage of 0-1V, current density of 1A / g, charge and discharge cycle number of 2000 times, and the capacity retention rate after 2000 cycles was calculated.
[0061] Table 1 Performance test results
[0062]
[0063] It can be seen from the examples in Table 1 and comparative example 3 that sulfur / nitrogen doping can produce more active sites that are beneficial to charge storage and transfer, and can also cause redox reactions during the charge and discharge process to produce pseudocapacitance, which is beneficial to the improvement of specific capacitance and energy density.
[0064] It can be seen from Table 1, Example 1, Example 5, Example 6, Comparative Example 1, and Comparative Example 2 that the change of the soft template of the present invention has a significant effect on the specific surface area, pore structure and energy density of the ordered mesoporous carbon, further verifying the previous speculation that the compounding ratio of sodium dodecyl sulfate and F127 in the soft template affects the interaction between the carbon source modified phenolic resin and the triblock copolymer, thereby affecting the pore structure of the ordered mesoporous carbon.
[0065] Through the cycle life test at a current density of 1A / g, after 2000 charge and discharge cycles, the capacitor retained more than 88% of its capacitance, indicating excellent electrochemical stability.
[0066] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A method for preparing sulfur / nitrogen doped ordered mesoporous carbon materials, characterized in that: The steps include: S1: Add phenol and aminothiophene compounds to a reaction kettle and mix them evenly, heat up and keep the temperature constant for the first time, drop formaldehyde aqueous solution, heat up and keep the temperature constant for the second time after the dropwise addition, and distill after the reaction to obtain a viscous liquid phenolic modified amine; S2: heating phenol to melt, adding phenolic modified amine and mixing evenly, adding alkali solution and formaldehyde aqueous solution and mixing evenly, heating to react, cooling to room temperature after the reaction, adjusting pH, vacuum dehydration, and adding organic solvent to prepare a modified phenolic resin solution; S3: dissolving a soft template in an organic solvent to prepare a template solution, adding a modified phenolic resin solution and mixing evenly, standing, drying, and carbonizing at high temperature to obtain a sulfur / nitrogen doped ordered mesoporous carbon material; the soft template is compounded from a sulfate anionic surfactant and a triblock copolymer in a mass ratio of 0.08-0.1:
1.
2. The method for preparing sulfur / nitrogen doped ordered mesoporous carbon material according to claim 1, characterized in that: In step S1, the aminothiophene compound is selected from one or a combination of two or more of 1-thiophene-2-ylpropane-1-amine, 1-(thiophene-3-yl)ethylamine, 4-methyl-3-thiopheneamine, 2-thiophenemethylamine, 2-thiopheneethylamine, 3-thiophenemethylamine, and 3-thiopheneethylamine; preferably 2-thiophenemethylamine.
3. The method for preparing sulfur / nitrogen doped ordered mesoporous carbon materials according to claim 1, characterized in that: In step S1, the molar ratio of phenol, formaldehyde and aminothiophene compound is 1-1.2:1-1.5:1-1.5; the first temperature is raised to 60-80°C; the concentration of the formaldehyde aqueous solution is 30-37wt%; the formaldehyde solution is dripped in 0.5-1h, the second temperature is raised to 100-105°C, and the reaction time is 3-5h.
4. The method for preparing sulfur / nitrogen doped ordered mesoporous carbon material according to claim 1, characterized in that: In step S2, the mass ratio of the phenol, the phenol-modified amine, the alkali solution, and the formaldehyde aqueous solution is 1:0.4-0.6:0.30-0.35:2-2.
2.
5. The method for preparing sulfur / nitrogen doped ordered mesoporous carbon material according to claim 1, characterized in that: In step S2, the concentration of the alkali solution is 15-20wt%, and the alkali solution is selected from one or a combination of two or more of potassium hydroxide aqueous solution, sodium hydroxide aqueous solution, potassium carbonate aqueous solution, and sodium carbonate aqueous solution; the concentration of the formaldehyde aqueous solution is 30-37wt%.
6. The method for preparing sulfur / nitrogen doped ordered mesoporous carbon material according to claim 1, characterized in that: In step S2, the temperature is raised to 70-80° C. for 3-5 hours; the pH is adjusted to a neutral pH using a 0.5-1 mol / L HCl solution; the organic solvent is selected from one or a combination of two or more of tetrahydrofuran, ethanol, methanol, isopropanol, n-butanol, and ether; and the concentration of the modified phenolic resin solution is 15-25wt%.
7. The method for preparing sulfur / nitrogen doped ordered mesoporous carbon material according to claim 1, characterized in that: In step S3, the triblock copolymer is selected from one or a combination of F127 and P123; the sulfate anionic surfactant is selected from one or a combination of sodium dodecyl sulfate and sodium nonylphenol polyoxyethylene ether sulfate.
8. The method for preparing sulfur / nitrogen doped ordered mesoporous carbon material according to claim 1, characterized in that: In step S3, the mass ratio of the soft template to the modified phenolic resin is 10-15:100; and the concentration of the soft template in the template solution is 5-8wt%.
9. The method for preparing sulfur / nitrogen doped ordered mesoporous carbon material according to claim 1, characterized in that: In step S3, the organic solvent is selected from one or a combination of two or more of tetrahydrofuran, ethanol, methanol, isopropanol, n-butanol, and diethyl ether; the standing is standing at 20-30° C. for 5-10 hours, and the drying is drying at 80-100° C. for 10-24 hours.
10. Use of the sulfur / nitrogen doped ordered mesoporous carbon material prepared by the method for preparing the sulfur / nitrogen doped ordered mesoporous carbon material according to any one of claims 1 to 9 as a supercapacitor electrode material.
Citation Information
Patent Citations
High-thermostability ordered mesoporous carbon material and preparation method thereof
CN102275898B
A kind of preparation method of ordered mesoporous carbon material
CN105540566B